Dosimetria em tomografia computadorizada para controle de dose em órgãos radiossensíveis utilizando um phantom antropomórfico - Souza, Isabela Oliveira (2019)
Computed tomography (CT) is one of the current most used imaging methods. In spite of the technological advances, it is necessary to continue performing dosimetry measurements, trying to keep the dose as low as possible and preserving the standard of diagnostic quality of the exam. The objective of this study is to evaluate doses in radio-sensitive organs (crystalline, thyroid, breast, male and female gonads and skin) using an anthropomorphic simulator Alderson Rando, male model, with an accessory simulating the breast. To perform the measurements, thermoluminescent dosimeters (TLD) of the LiF: Ti,Mg type were used. They were calibrated with 120 kV energy. The tests were performed on two devices: a 128 slices Siemens Somaton Definition AS+ scanner and a 512 slices GE Revolution CT. The protocols used in the exposures were head, chest, abdomen and coronaries, the same routinely applied in the clinic. For each protocol, two pairs of dosimeters were positioned in the radio sensitive regions, and one pair in the isocenter region of the protocol to determine the entrance skin dose. After the exposures, the dosimeters were placed in a RA'94 model reader in order to obtain the absorbed dose. The equivalent doses received in each organ were calculated and the values of volume computed tomography dose index (CTDIvol) and dose length product (DLP) provided by the equipment in each protocol were recorded. Results for the absorbed dose show that the lens is the organ receiving the highest dose in the two devices, both in the head protocol. In the GE scanner, the dose is approximately 30.9 mSv and the Siemens CT is 26.5mSv. Comparing CTDIvol and DLP results of this work with other studies in different equipment, Siemens and GE obtained better results for the abdomen protocol with all values below those in the literature.For the chest protocol, GE has the best result compared to Siemens, which exceeds the best value found in the studies in 22% for CTDIvol and 4.1% for DLP. For the head protocol, the equipment with the best result was Siemens with the values of CTDIvol 250.1% lower than that of the literature and DLP 44,0% below them. Compared with the studies presented, the two devices performed with doses below the American College of Radiology (ACR) reference limits for the head and abdomen protocols. The results obtained in this study show the good performance of the protocols applied, resulting in doses that contribute to meet expected or lower risk limits for the radio-sensitive organs.